2020
DOI: 10.1177/0954411920926077
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula maturation and the influence of fluid dynamics

Abstract: Arteriovenous fistula creation is the preferred vascular access for haemodialysis therapy, but has a large failure rate in the maturation period. This period generally lasts 6 to 8 weeks after surgical creation, in which the vein and artery undergo extensive vascular remodelling. In this review, we outline proposed mechanisms for both arteriovenous fistula maturation and arteriovenous fistula failure. Clinical, animal and computational studies have not yet shown a definitive link between any metric and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 106 publications
0
8
0
2
Order By: Relevance
“…Patients were recruited at Prince of Wales Hospital, Sydney, Australia, with approval from the Human Research Ethics Committee (HREC ref: 15/063), as part of an going study (Colley et al 2020). A 56-year-old male patient, scheduled for fistula creation surgery (and not currently on dialysis), agreed to attend the clinic on a weekly basis to enable scans to be conducted.…”
Section: Patient Informationmentioning
confidence: 99%
“…Patients were recruited at Prince of Wales Hospital, Sydney, Australia, with approval from the Human Research Ethics Committee (HREC ref: 15/063), as part of an going study (Colley et al 2020). A 56-year-old male patient, scheduled for fistula creation surgery (and not currently on dialysis), agreed to attend the clinic on a weekly basis to enable scans to be conducted.…”
Section: Patient Informationmentioning
confidence: 99%
“…Consequently, although several factors can affect AVF maturity, detailed preoperative evaluation and skilled surgical technique are paramount. The impact of drugs (including antiplatelet drugs, fish oils, statins, and beraprost) on AVF is currently inconclusive, 1 , 62 , 76 , 77 , 78 , 79 , 80 , 81 and the expert group believes that they can be selectively administered as an auxiliary measure, although individualized assessment of indications and contraindications should be conducted for patients with multiple coexisting diseases.…”
Section: Description Of the Consensusmentioning
confidence: 99%
“…Unfortunately, fistula creation often leads to complications and morbidity in these patients. Colley et al 2 have revised the literature and outline the proposed mechanisms for both AVF maturation and AVF failure. Authors conclude that neither clinical, animal nor computational studies have not yet shown a definitive link between any investigated metric and disease development.…”
Section: Physiological Fluid Mechanics: a Special Issue With A Tastermentioning
confidence: 99%